2004
DOI: 10.1159/000076570
|View full text |Cite
|
Sign up to set email alerts
|

Sledding Accidents in Children: Potential for Serious Injury, Risk of Fatality

Abstract: Though a pastime rarely considered rough or dangerous, sledding is not risk-free. The presentation of several serious injuries to Rainbow Babies and Children’s Hospital in Cleveland, Ohio, led us to examine our emergency department and admitting records to determine the incidence of neurological injury among children involved in sledding accidents. We discovered 24 children who had sustained brain or spine injuries as sequelae to sledding mishaps during a 5-year period. The ages ranged from 3 months to 15 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…13,15 Collisions with a stationary object were responsible for the majority of sledding injuries in this study. This finding is consistent with previously reported data regarding sledding injuries 3,11,16,17 as well as fatal skiing and snowboarding injuries. 18 In our study, there was no significant difference in the proportion of injuries caused by collisions among age groups.…”
Section: Discussionsupporting
confidence: 93%
“…13,15 Collisions with a stationary object were responsible for the majority of sledding injuries in this study. This finding is consistent with previously reported data regarding sledding injuries 3,11,16,17 as well as fatal skiing and snowboarding injuries. 18 In our study, there was no significant difference in the proportion of injuries caused by collisions among age groups.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple investigators have reported major head trauma related to sledding, including skull fractures, 7,8,11,13,15,17,21 cerebral contusion, 11 and intracerebral hemorrhage. 7,9,13,17 Deaths resulting from head trauma in victims of sledding accidents have also been reported, 9,10,[12][13][14] although these are rare. As with many other types of traumatic fatalities, head trauma appears to be a major contributor to sledding-related fatalities.…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of head injuries found in this study suggests that the use of helmets could be recommended for children participating in sledding; although data on helmet use were not available for this study, investigators in the United States and Canada who have examined this issue found helmet use exceedingly rare (0-7%) among injured sledders. 1,6,8,[10][11][12]16,17 Whether standard, existing helmets (e.g., bicycle or ski helmets) would be adequate for this purpose or whether some engineering modification is required remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…4 Sledding-related injuries can be mild (eg, lacerations) to more severe (eg, fractures and traumatic brain injuries) and can lead to hospitalization, permanent disability, and death. 1,3,[5][6][7][8][9][10] Although many studies have examined injuries associated with snow sports, such as snowboarding and skiing, [11][12][13][14][15][16][17][18] only a few studies have exclusively examined sledding-related injuries. 1,3,7,8,[19][20][21][22][23] Although sledding-related injury studies have identified important findings regarding the characteristics of patients (eg, age and sex), types of injuries (eg, fractures), mechanism of injury (eg, collision), and a lack of safety awareness (eg, not wearing a helmet), 1,3,6,7,22 many have significant limitations.…”
Section: Introductionmentioning
confidence: 99%